Pharyngeal bulb reduction program in individuals with cleft palate - Aferri, Homero Carneiro (2024)
Introduction: This study aimed to implement a Pharyngeal Bulb Reduction Program (PBRP) and analyze its effect on the configuration of the pharyngeal bulb. PBRP was performed by a team of dentists and speech therapists with the goal of reducing the dimensions of the pharyngeal bulb in patients rehabilitated with pharyngeal obturators who presented normal speech. The reduction of the bulb aims to stimulate better functioning of the Velopharyngeal Mecanism (VPM) function, reversing a condition of velopharyngeal hypodynamism, which would allow for the surgical rehabilitation of Velopharyngeal Dysfunction (VPD). Objectives: a) Describe the Pharyngeal Bulb Reduction Program (PBRP) to reduce the size of the velopharyngeal orifice in individuals with operated cleft palate; b) Verify the effect of PBRP on the configuration of the pharyngeal bulb. Materials and Methods: The sample consisted of 13 patients, from a convenience sample of individuals of both sexes, with operated congenital cleft palate or cleft lip and palate. They underwent prosthetic treatment for velopharyngeal insufficiency using a pharyngeal obturator. Patients who met the inclusion criteria underwent a pharyngeal bulb reduction program, specially designed for this study, consisting of bulb reductions during nasoendoscopy and intensive speech therapy sessions after each bulb reduction to recover normal speech and allow for a new reduction. Measurements of the length, width, area, volume of the bulb, and total weight of the palate prosthesis were taken before and after each pharyngeal bulb reduction. Results: The results showed a statistically significant reduction (p <0.05) in all measures for the 13 patients, namely: a) mean bulb length from 23.68 mm pre- PBRP to 12.21 mm post-PBRP, a reduction of 47.26%; b) mean bulb width from 17.38 mm pre-PBRP to 11.93 mm post-PBRP, a reduction of 32.13%; c) mean bulb area from 328.01 mm2 pre-PBRP to 126.63 mm2 post-PBRP, a reduction of 31.41%; d) mean bulb volume from 3443.27 mm3 pre-PBRP to 1609.23 mm3 post-PBRP, a reduction of 52.80%; e) mean prosthesis weight from 12.23 g to 9.61 g post-PBRP, a reduction of 21.12%. Conclusions: PBRP proved to be an effective approach in reducing the pharyngeal bulb and consequently decreasing the velopharyngeal orifice in patients with hypodynamic velopharynx.